Pengaruh Penyuluhan Kesehatan dengan Menggunakan Leaflet terhadap Pengetahuan Tinea Versicolor di SMA N 1 Semende Kabupaten Muara Enim Tahun 2023 - Rina Aslamia; Sabtian Sarwoko; Fera Meliyanti (Pusat Riset dan Inovasi Nasional, 2024)
Introduction: Tinea vesicolor is a skin disorder caused by Malasezia furfur infection in the form of a chronic superficial fungal infection. Tinea versicolor is endemic which is widely found globally in developed and developing countries with tropical and subtropical climates and can attack people regardless of certain age groups. Objective: To determine the effect of health education using leaflets on knowledge of Tinea versicolor at SMA N 1 Semende, Muara Enim Regency in 2023 Methods: The research design used was a quasi-experimental pre-test and posttest. The population in this study were 177 students in class X SMA N 1 Semende, Muara Enim Regency. The sample in this study used the Accidental Sampling technique. Results: From the results of the analysis, the average value after the post test was 11,80 ≥ the pre test value was 8,90. The results of bivariate analysis obtained a p value of 0.000. This means that there is a difference in the average value of students before and after counseling. Conclusion: There is an effect of health education using leaflets on Tinea versicolor knowledge at SMA N 1 Semende, Muara Enim Regency in 2023 with the results of the paired t test statistic of 0.000.